Operational Non-Contact Diagnostics of Induction Machine Based on Stray Electromagnetic Field - Bernat, Petr; Kacor, Petr (Communications - Scientific Letters of the University of Zilina, 2015)
Paper deals with one new method of testing and operational diagnostics of induction machines using a stray electromagnetic field. This leakage field on the surface or on surroundings of machine frame is the carrier for diagnostic information and we can make simultaneous comparisons of utility, advantages and disadvantages of the existing and most common methods of diagnostics performed using the measurement of the machine supply current. This method is patented as Czech Patent CZ 303 470, UPV 2012.
Keywords: induction machine; asynchronous motor; functional testing; technical diagnostics; frequency spectrum; current spectrum; stray electromagnetic field; leakage electromagnetic field